Hubungan Asupan Zink, Magnesium, dan Serat dengan Kadar Gula Darah Puasa Pasien Diabetes Mellitus Tipe 2 di RS PKU Muhammadiyah Temanggung - Efina Amanda; Salsa Bening (Jurnal Gizi, 2019)
Diabetes Mellitus (DM) type 2 occurs because of insulin resistance, on of the contributing factors is the lack of intake of micronutrients (zinc and magnesium) and macro (fiber). The prevalence of DM in Temanggung is 1,6%. There are 45 patients suffering from type 2 diabetes at PKU Muhammadiyah Hospital in Temanggung which have zinc, magnesium, and fiber intake below normal (deficit). The study aims to analyze the relationship of zinc, magnesium, and fiber intake with fasting blood sugar levels at PKU Muhammadiyah Hospital in Temanggung. The research is a cross sectional design with 45 responden taken with purposive sampling technique. Statistical analysis using kolmogorov smirnov normality test was tested using the spearman correlation test. Data collection of zinc, magnesium, and fiber intake using the 2x24 hour recall and FFQ form while the blood sugar level data is obtained from the patient’s medical record book. The result showed that there was a relationship between zinc intake to fasting sugar levels of patients (p=0,000), there was a correlation between magnesium intake to fasting blood sugar levels in patients (p=0,000). There is a relationship between zinc, magnesium, and fiber intake to fasting blood sugar levels. Keywords: Zink Intake, Magnesium Intake, Fiber Intake, Fasting Blood Sugar Level, Type 2 Diabetes Mellitus